2003
DOI: 10.1073/pnas.1531645100
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the triple tryptophan electron transfer chain in Escherichia coli DNA photolyase: Trp382 is the primary donor in photoactivation

Abstract: In Escherichia coli photolyase, excitation of the FAD cofactor in its semireduced radical state (FADH • ) induces an electron transfer over Ϸ15 Å from tryptophan W306 to the flavin. It has been suggested that two additional tryptophans are involved in an electron transfer chain FADH • 4 W382 4 W359 4 W306. To test this hypothesis, we have mutated W382 into redox inert phenylalanine. Ultrafast transient absorption studies showed that, in WT photolyase, excited FADH • decayed with a time constant Ϸ 26 ps to full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(165 citation statements)
references
References 36 publications
13
150
1
1
Order By: Relevance
“…1). Photolyases provide three conserved tryptophan residues, which were supposed to be involved in electron transport to reduce the FADH 2 (Byrdin et al, 2003, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Photolyases provide three conserved tryptophan residues, which were supposed to be involved in electron transport to reduce the FADH 2 (Byrdin et al, 2003, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…PCC6803 (Brudler et al, 2003;bottom line). The black boxed tryptophans are believed to be involved in intraprotein electron transport (Byrdin et al, 2003). The lengths of the proteins are indicated in parentheses.…”
Section: Methodsmentioning
confidence: 99%
“…In the former, Brettel has demonstrated that FAD initiates oxidation of Trp382, which engages in a hole-hopping oxidation of Trp359 and finally Trp306, which deprotonates to yield the neutral tryptophan radical [1,[178][179]. For the oxidation of the terminal Trp306 found in E. coli photolyase, Schelvis and coworkers have demonstrated the electron transfer proceeds by concerted PCET below pH = 6.5, but otherwise undergoes stepwise PCET via an initial electron transfer [180].…”
Section: Indolesmentioning
confidence: 99%
“…It is well established that multi-step tunnelling, called hopping, is required for functional charge transport in many redox enzymes (examples include ribonucleotide reductase [1][2][3][4][5][6][7][8][9], photosystem II [10][11][12], DNA photolyase [13][14][15][16][17][18][19][20][21], MauG [22][23][24][25] and cytochrome c peroxidase [26,27]). Here, we advance the hypothesis that many such enzymes, most especially those that generate high-potential intermediates during turnover, could be irreversibly damaged if the intermediates are not inactivated in some way.…”
Section: Introductionmentioning
confidence: 99%